Characteristics and dolomitization of the Lower Qiulitage Group reservoir in Bachu Uplift, Tarim Basin, China - Bin Li; Qingsong Xia; Jun Peng; Suju Yang; Qingqi Xu; Lei Zeng (Earth Sciences Research Journal)
The characteristics of the Lower Qiulitage Group in Bachu uplift, which originated in the Upper Cambrian period, are not clear. Based on four core observations, identification of 40 thin sections, and geochemical analysis of samples, this study concludes that crystal dolomite reservoirs developed in the Lower Qiulitage Group in Bachu uplift. Intercrystalline pores and dissolved pores formed the main reservoir space, while dissolution pores and fractures were developed in the middle and bottom part of the formation. The reservoir features low porosity and low permeability, and the fine-medium crystalline dolomite reservoir has the best pore structure. According to a petrochemical analysis, the Lower Qiulitage Group reservoir experienced intense dolomitization, with slightly higher content of trace elements Mn and Sr and negative oxygen isotropy. Tectonic hydrothermal dolomitization developed locally under the influence of base faults, and vug pores were filled with saddle dolomites and siliceous filling. The presence of rare earth elements Ce and Eu presented positive anomaly characteristics. It suggested that the CO2 acid dissolution caused by hydrothermal fluids may be a new mechanism for the increase in pores in deeply buried reservoirs, which is worth further study.